WILLINGNESS TO PAY FOR HOSPITAL PHARMACIST’S DISPENSING SERVICES: A CASE STUDY OF METTAPRACHARAK (WAT RAIKHING) HOSPITAL - CHEVADISAIKUL, TERACHART; KAPOL, NATTIYA (Thai Bulletin of Pharmaceutical Sciences, 2018)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อประเมินความเต็มใจที่จะจ่ายค่าบริการจ่ายยาของเภสัชกรโรงพยาบาล และหาปัจจัยที่มีผลต่อความเต็มใจที่จะจ่ายค่าบริการเภสัชกรของผู้ป่วยนอกโรงพยาบาลเมตตาประชารักษ์ (วัดไร่ขิง) จ.นครปฐม เก็บข้อมูลโดยใช้แบบสอบถามที่ผู้วิจัยพัฒนาขึ้น โดยการสัมภาษณ์แบบตัวต่อตัว การหาความเต็มใจที่จะจ่ายใช้เทคนิค bidding game กลุ่มตัวอย่างใช้วิธีสุ่มอย่างเป็นระบบจากผู้ป่วยนอกโรงพยาบาลเมตตาประชารักษ์ (วัดไร่ขิง) ที่มารับบริการระหว่าง เดือนมีนาคม ถึง เมษายน พ.ศ. 2560 จำนวน 368 คน ผลการศึกษาพบว่า ร้อยละ 97.3 มีความเต็มใจที่จะจ่ายค่าบริการจ่ายยาของเภสัชกร ค่ามัธยฐานของความเต็มใจที่จะจ่ายเท่ากับ 100 บาท ค่าพิสัยของควอไทล์เท่ากับ 130 บาท ผลการวิเคราะห์การถดถอยเชิงเส้นพหุ พบว่ารายได้ส่วนบุคคล รายได้ครัวเรือน (p<0.05) และโรคที่มารับการรักษา (p<0.001) มีผลต่อความเต็มใจที่จะจ่ายค่าบริการจ่ายยาของเภสัชกรอย่างมีนัยสำคัญทางสถิติ กลุ่มตัวอย่างให้คำแนะนำว่าเวลาที่เหมาะสมในการให้คำปรึกษาด้านยาคือ 5-10 นาที จากผลการศึกษาในครั้งนี้ผู้ป่วยส่วนใหญ่ยินดีที่จะจ่ายค่าบริการจ่ายยาของเภสัชกรโรงพยาบาล และให้มูลค่าที่สูง The aims of this study were to measure outpatients’ willingness to pay (WTP) for hospital pharmacists’ dispensing services at Mettapracharak (Wat Raikhing) Hospital and to determine the factors influencing their WTP. A questionnaire was used to collect data during face to face interviews. Their WTP was measured using a bidding game technique. Three hundred and sixty-eight participants were systematically sampled from outpatients at Mettapracharak (Wat Raikhing) Hospital from March to April 2017. The results showed that 97.3% of samples were willing to pay for the hospital pharmacists’ dispensing services. The median of the patients’ WTP was 100 baht and the interquartile range was 130 baht. Multiple linear regression analysis revealed that the patients’ income, household income (p<0.05) and disease (P<0.001) were statistically significant relating to the WTP for hospital pharmacists’ dispensing service. Most participants suggested that the time that was appropriate for counseling was 5-10 minutes. The results from this study concluded that most patients were willing to pay for hospital pharmacists’ dispensing services of high value.